2016
DOI: 10.1155/2016/4580323
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α T-857C (rs1799724) Polymorphism and Risk of Cancers: A Meta-Analysis

Abstract: Objectives. To investigate the potential association of tumor necrosis factor-α T-857C polymorphism with susceptibility to the five common malignant tumors. Materials and Methods. A comprehensive search of PubMed/Medline, Embase, and Web of Science databases was performed up to November 2015. Pooled odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated to assess the strength of the association. Subgroup analysis, heterogeneity analyses, and publication bias were also texted in the meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The haplotypic frequencies of the other genes showed no statistically significant difference between the groups. In the TNF gene, the TCG haplotype (rs1799964, rs1799724, and rs361525, respectively) contained risk alleles associated with low TNF expression [ 15 , 16 , 17 , 18 ]. The frequency of this haplotype was compared between cases and controls, but there was no statistically significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…The haplotypic frequencies of the other genes showed no statistically significant difference between the groups. In the TNF gene, the TCG haplotype (rs1799964, rs1799724, and rs361525, respectively) contained risk alleles associated with low TNF expression [ 15 , 16 , 17 , 18 ]. The frequency of this haplotype was compared between cases and controls, but there was no statistically significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Cen and Wu [25] and Wang et al [26] both showed that TNF-α -857 C/T polymorphism is significantly associated with increased risk of GC. However, TNF-α -1031 and TNF-α -863 polymorphisms have neither the meta-analysis, they were just reported in signal case–control: Hamajima et al [27] found -1031CC was not only related with reduced items, such as sex, age, but also low seropositivity.…”
Section: Introductionmentioning
confidence: 99%
“…Heidari, Moudi, Mahmoudzadeh Sagheb, and Moudi () also found that the TNF‐α rs1799724 CC/CT genotypes are associated with susceptibility to HBV infection in a South East Iranian Population. A meta‐analysis of 5,215 cases and 6,755 controls reported that the TNF‐α rs1799724 polymorphism could increase HCC risk in homozygote and recessive genetic models in Asian, Caucasian and African populations (Wang, Wang, Yu, & Li, ). However, in this study, we did not find an association between rs1799724 and HCC in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%